Organic modified magnetic bentonite as well as preparation method and application thereof

Organic modified magnetic bentonite (TPMB) was prepared by loading γ-Fe2O3 magnetic particles and using TPODAC for surface modification, which solved the problems of insufficient affinity and difficulty in adsorbing organic pollutants, and achieved efficient adsorption and the effect of rapid magnetic separation.

CN119455887APending Publication Date: 2025-02-18SHANGHAI INST OF TECH

Patent Information

Application Number
CN202411867177.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When existing bentonite adsorb organic pollutants, the affinity performance is insufficient and the separation is difficult, making it difficult to effectively remove organic pollutants such as pyroxolamine.

Method used

Organic modified magnetic bentonite clay (TPMB) was prepared by loading γ-Fe2O3 magnetic particles and surface modification using 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride (TPODAC). . This material not only improves the adsorption performance of protoxolamine, but also achieves rapid magnetic separation under an external magnetic field.

Benefits of technology

TPMB shows high efficiency in adsorption of protoxamine, with an adsorption efficiency of up to 52.16%, and remains stable within different pH ranges. It can be quickly recovered by magnetic separation, and has the advantages of efficient adsorption and multiple recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455887A_ABST
    Figure CN119455887A_ABST
Patent Text Reader

Abstract

The invention relates to organic modified magnetic bentonite as well as a preparation method and application thereof, and the organic modified magnetic bentonite is a ternary composite material which takes bentonite as a carrier to load gamma-Fe2O3 magnetic particles and is subjected to surface modification by using an organic modifier 3-(trimethoxysilyl) propyl-N-octadecyl dimethyl ammonium chloride (TPODAC). Compared with the prior art, the organic modified magnetic bentonite disclosed by the invention not only can improve the adsorption performance of pretilachlor, but also can realize rapid magnetic separation of an adsorbent under the condition of an external magnetic field, so that the adsorbent can be recycled for multiple times. The adsorbent organic modified magnetic bentonite has the advantages of efficient adsorption and rapid recovery, the preparation method is simple and easy to implement, and the adsorbent organic modified magnetic bentonite shows great application potential in treatment of pretilachlor wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental pollution control, and in particular to an organic modified magnetic bentonite and a preparation method and application thereof. Background Art

[0002] Rice is the largest staple food crop in my country. The rice production in my country has remained stable at 2.10 for 11 consecutive years. 8 Among various rice herbicides, pretilachlor, a highly selective rice paddy herbicide, is widely used in my country to control weeds in rice paddies. Due to the large amount of water used in rice field irrigation, reservoirs, and drainage, it easily enters natural rivers at a high rate. Pretilachlor is highly toxic to aquatic organisms such as fish and shellfish, and poses a phytotoxic risk to rice. Low concentrations of pretilachlor in the environment may enter the human body through the food chain, causing harm to the human body.

[0003] Bentonite, a natural adsorbent, is a hydrous clay mineral primarily composed of montmorillonite. It offers advantages such as environmental friendliness and abundant reserves, and holds great potential in water treatment. Natural bentonite's adsorption of metal ions and inorganic compounds relies primarily on its interlayer ion exchange capacity and large surface area, resulting in excellent water absorption and swelling properties. However, due to its poor affinity for organic matter, bentonite is not very effective in adsorbing organic pollutants. Furthermore, its high dispersibility in water poses significant challenges for subsequent solid-liquid separation. Therefore, when using bentonite as an adsorption carrier to remove organic pollutants, it undergoes organic and magnetic modification to enhance its adsorption and solid-liquid separation properties before conducting adsorption tests.

[0004] Organic magnetic bentonite materials not only retain their inherent adsorption and high suspension properties, but also allow organic surface modifiers to interact with pollutants, thereby achieving water purification. Quaternary ammonium ions are one of the most commonly used ions in organic modification, increasing bentonite's affinity for hydrophobic organic compounds, including neutral and even acidic pesticides. Cetyltrimethylammonium bromide (CTAB) and other traditional quaternary ammonium salts, commonly used organic modifiers, typically bind to bentonite via a single ion exchange mechanism, which is not robust and presents certain drawbacks. 3-(Trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride (TPODAC), a relatively new organic modifier, often covalently bonds with various inorganic compounds. This stable binding mechanism makes it suitable for adsorbent modification. Currently, there are no studies using TPODAC to modify bentonite. However, the use of TPODAC to modify bentonite, investigate its mechanism, and verify its adsorption capacity for pretilachlor, holds great research value.

[0005] Chinese patent CN201711241239.8 discloses a method for preparing organically modified magnetic alkaline calcium bentonite. This method involves preparing magnetic nanoparticles of Fe₃O₄ and then loading them onto alkaline calcium bentonite to produce the magnetic alkaline calcium bentonite. The surface of the magnetic alkaline calcium bentonite is then organically modified using a copolymer film of sodium carboxymethyl cellulose and chitosan, a non-toxic and environmentally friendly modifier. The organically modified magnetic alkaline calcium bentonite exhibits high water absorption, with an expansion coefficient exceeding 40 times after water absorption. The structure contains abundant hydrophilic groups, such as hydroxyl groups, which impart strong hydrophilicity and dispersibility, allowing it to remain suspended in water for extended periods. Furthermore, the material exhibits stable performance, with functional groups such as carboxyl and hydroxyl groups only gradually breaking down at temperatures above 300°C, allowing interlayer water to escape. It is essentially insoluble in water, slightly soluble in strong acids and bases, and is resistant to strong oxidants and reducing agents, demonstrating excellent chemical stability. Summary of the Invention

[0006] The present invention is directed to an organically modified magnetic bentonite (TPMB), its preparation method, and its application. The organically modified magnetic bentonite is used to investigate its adsorption capacity for pretilachlor. The organically modified magnetic bentonite not only improves its adsorption performance for pretilachlor but also enables rapid magnetic separation of the adsorbent under an external magnetic field, thereby enabling multiple recycling. The organically modified magnetic bentonite adsorbent of the present invention simultaneously offers the advantages of efficient adsorption and rapid recovery, is simple to prepare, and exhibits significant potential for treating pretilachlor wastewater.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] The invention discloses an organic modified magnetic bentonite, which is a ternary composite material which uses bentonite as a carrier, loads γ-Fe2O3 magnetic particles, and is surface modified with an organic modifier 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride (TPODAC).

[0009] Furthermore, the organically modified magnetic bentonite can maintain good thermal stability within the range of 200° C. to 800° C., has a saturation magnetization intensity of 43.93 emu / g, and can achieve solid-liquid separation under the action of an external magnetic field.

[0010] As a preferred technical solution, the external magnetic field is applied for less than 20 seconds.

[0011] The present invention also provides a method for preparing organically modified magnetic bentonite. The method adopts a coprecipitation method to prepare magnetic γ-Fe2O3 particles, which are then loaded onto bentonite to obtain magnetic bentonite. 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride is then used for surface modification to obtain TPMB.

[0012] Furthermore, the specific steps of the method for preparing the organically modified magnetic bentonite are as follows:

[0013] S1, preparing RB dispersion;

[0014] S2, preparation of Fe 2+ and Fe 3+ A mixed solution;

[0015] S3, preparation of magnetic bentonite: the Fe-containing 2+ and Fe 3+ The mixed solution is added to the RB dispersion prepared in step S1, the pH is adjusted, magnetic stirring is performed under heating conditions in a water bath, and the mixture is filtered, washed, and dried to obtain magnetic bentonite (MB) loaded with γ-Fe2O3;

[0016] S4, preparing a mixed dispersion: dissolving the magnetic bentonite prepared in step S3 in a solvent, adding 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride after ultrasonication, and ultrasonicating for a second time to obtain a mixed dispersion;

[0017] S5. Preparation of organically modified magnetic bentonite: stirring and condensing the mixed dispersion prepared in step S4 under heating conditions in a water bath, filtering, washing, and drying to obtain organically modified magnetic bentonite.

[0018] Furthermore, in step S1, the preparation method of the RB dispersion is as follows:

[0019] Unmodified bentonite (RB) was dispersed in deionized water and magnetically stirred under heating conditions in a water bath to form a RB dispersion.

[0020] Furthermore, the solid-liquid ratio of the bentonite to deionized water is 1:(5-10),

[0021] The water bath heating temperature is 40-60° C., and the magnetic stirring time is 30-40 min.

[0022] Furthermore, in step S2, the Fe 2+ and Fe 3+ The preparation method of the mixed solution is as follows:

[0023] Ferrous sulfate heptahydrate and ferric chloride hexahydrate were dissolved in deionized water to form a solution containing Fe 2+ and Fe 3 + of mixed solution.

[0024] Furthermore, the mixed solution contains Fe 2+ with Fe 3+ The molar ratio is 1:(1.5-2.5), preferably 1:2.

[0025] Furthermore, in step S3, the Fe 2+ and Fe 3+ The volume ratio of the mixed solution and the RB dispersion prepared in step S1 is 1:(1-2);

[0026] The pH regulator is concentrated ammonia and hydrochloric acid, and the pH adjustment range is 10 to 12;

[0027] The water bath heating temperature is 50-70°C, and the magnetic stirring time is 50-70 minutes;

[0028] The detergent is deionized water;

[0029] The drying temperature is 60-80° C., and the drying time is 20-30 hours.

[0030] Furthermore, in step S4, the solid-liquid ratio of the magnetic bentonite to the solvent is 1:(90-110);

[0031] The solvent is an ethanol / water solution, and the volume ratio of the ethanol to water is (2-4):1;

[0032] The cation exchange capacity (CEC) of the magnetic bentonite is 498.26-523.40 mmol / kg;

[0033] The mass concentration of the 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride is 50% to 70%;

[0034] The dosage of the 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride is 20%-150% of the cation exchange capacity of the magnetic bentonite;

[0035] The ultrasonic time is 30 to 50 minutes, the secondary ultrasonic time is 20 to 40 minutes, and the ultrasonic frequency is 30 to 50 kHz.

[0036] Furthermore, in step S5, the water bath heating temperature is 50-70° C., the stirring time and the condensation reflux time are 4-6 hours,

[0037] The washing solvent is an ethanol / water solution, and the volume ratio of the ethanol to water is (2-4):1;

[0038] The drying temperature is 20-40° C., and the drying time is 20-30 hours.

[0039] In addition, the present invention also provides an application of an organically modified magnetic bentonite, wherein the organically modified magnetic bentonite is used for adsorbing pretilachlor.

[0040] As a preferred technical solution, the organically modified magnetic bentonite is used to remove pretilachlor in acidic or alkaline water bodies.

[0041] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0042] (1) The present invention loads 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride (TPODAC) on γ-Fe2O3 bentonite. The FTIR and XRD results show that TPODAC and γ-Fe2O3 have been successfully inserted into the bentonite interlayer. Compared with the unmodified bentonite, the edge of the TPMB composite material becomes looser with the loading of γ-Fe2O3 and TPODAC. Part of TPODAC is bound to MB through ion exchange, and the other part is connected to MB through covalent bonds, which is more stable than the traditional single ion exchange binding method. The results of VSM show that the experimentally prepared γ-Fe2O3-loaded bentonite still has good magnetic properties after organic modification and can meet the needs of rapid recovery.

[0043] (2) The organically modified magnetic bentonite TPMB of the present invention has good adsorption performance for pretilachlor, with an adsorption efficiency of up to 52.16% and a saturated adsorption capacity of up to 52.16 mg / g. The adsorption process is less affected by pH, and within the pH range of 2-10, the adsorption efficiency fluctuates within 10%.

[0044] (3) Compared with the reference document, the present invention first uses γ-Fe2O3 particles of natural bentonite for magnetization. Compared with the Fe3O4 particles used in the reference document, the magnetic γ-Fe2O3 particles used in the present invention are more stable and not easy to oxidize. The measured magnetization to saturation intensity (43.93emu / g) is much higher than the minimum saturation magnetization intensity (16.3emu / g) for separation and recovery, making it easier to separate in water. Secondly, the present invention uses organosilicon quaternary ammonium salt (TPODAC) as an organic modifier. Compared with the strong hydrophilic glycopolymer used in the reference document, the functional groups in the TPODAC structure have dual effects of ion exchange and hydrophobicity, which can enhance the ion exchange effect of bentonite and show stronger adsorption capacity for organic pollutants. Through comparative studies, the organic modified magnetic bentonite (TPMB) prepared by the method of the present invention not only shows a high adsorption capacity for pretilachlor wastewater, but is also easy to separate and recover in water. The preparation method is simple, the chemical properties are stable, and it has the potential to adsorb a variety of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is the magnetic hysteresis loop test diagram (VSM) of the organically modified magnetic bentonite prepared in Example 3;

[0046] Figure 2 This is a thermogravimetric (TG) analysis chart of the organically modified magnetic bentonite prepared in Example 3;

[0047] Figure 3 Fourier transform infrared spectroscopy (FTIR) analysis chart of the unmodified bentonite, magnetic bentonite, and organically modified magnetic bentonite provided in Example 3;

[0048] Figure 4 X-ray diffraction (XRD) patterns of the unmodified bentonite, magnetic bentonite, and organically modified magnetic bentonite provided in Example 3;

[0049] Figure 5 The adsorption isotherm curves of 4-100 mg / L pretilachlor on the organically modified magnetic bentonite prepared in Examples 1-3 are shown;

[0050] Figure 6 The figure shows the removal effect of 100 mg / L pretilachlor by the organically modified magnetic bentonite prepared in Examples 1-3 at different pH values;

[0051] Figure 7 This is a scanning electron microscope (SEM) image of the organically modified magnetic bentonite prepared in Example 3. DETAILED DESCRIPTION

[0052] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0053] The following describes some embodiments of the present invention in detail with reference to the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments may be combined with each other.

[0054] Example 1

[0055] This embodiment provides a method for preparing organically modified magnetic bentonite, and the specific steps are as follows:

[0056] (1) Preparation of magnetic bentonite:

[0057] 10 g of unmodified bentonite (RB) was dispersed in 60 mL of deionized water, and the mixture was heated in a 50° C. water bath with magnetic stirring at a rotation speed of 120 rpm for 30 min to obtain a RB dispersion.

[0058] Dissolve 13.9015g of ferrous sulfate heptahydrate and 27.0301g of ferric chloride hexahydrate in 40mL of deionized water, where Fe 2+ with Fe 3+ The molar ratio is 1:2, after the ferrous sulfate heptahydrate and ferric chloride hexahydrate are completely dissolved; 2+ and Fe 3+ of mixed solution.

[0059] Contains Fe 2+ and Fe 3+ The mixed solution was added to the RB dispersion, heated to 60°C, and the pH was adjusted to 10 using concentrated ammonia and hydrochloric acid. The mixture was heated in a 60°C water bath at 120 rpm and magnetically stirred for 60 minutes, with the pH maintained at 10 throughout the process. It was observed that the color of the mixed solution darkened and a black precipitate was formed.

[0060] After the reaction, the solid was filtered and washed with deionized water until the pH of the filtrate reached 7, and then dried in an electric forced air drying oven at 70°C for 24 hours. The solid was ground and passed through a 100-mesh sieve to obtain γ-Fe2O3-loaded magnetic bentonite (MB).

[0061] (2) Preparation of mixed dispersion:

[0062] 1 g of the magnetic bentonite prepared in step (1) was dispersed in 100 mL of ethanol / water solution (the volume ratio of ethanol to water was 3:1), ultrasonicated at 40 kHz for 40 min, then 0.2225 mL of TPODAC solution (mass concentration was 60%) was added, and ultrasonicated at 40 kHz for 30 min to obtain a mixed dispersion;

[0063] (3) Preparation of organic modified magnetic bentonite (TPMB):

[0064] The mixed dispersion prepared in step (2) was stirred at 120 rpm in a water bath at 60° C. while being condensed and refluxed for 5 h;

[0065] Filter and wash four times with 50 mL of ethanol / water solution (volume ratio of ethanol to water is 3:1) until the filtrate is free of foam;

[0066] The mixture was dried in an electric forced air drying oven at 30°C for 24 hours, ground and passed through a 100-mesh sieve to obtain organically modified magnetic bentonite 80-TPMB.

[0067] Example 2

[0068] This example provides a method for preparing an organic modified magnetic bentonite. The steps are the same as those in Example 1, except that the amount of TPODAC solution used in step (2) is 0.2782 mL and organic magnetic bentonite 100-TPMB is obtained in step (3).

[0069] Example 3

[0070] This example provides a method for preparing an organic modified magnetic bentonite. The steps are the same as those in Example 1, except that the amount of TPODAC solution used in step (2) is 0.4171 mL and organic magnetic bentonite 150-TPMB is obtained in step (3).

[0071] Figure 7 This is a scanning electron microscope image of the organically modified magnetic bentonite prepared in Example 3. Figure 7 As shown in the scanning electron microscope image, γ-Fe₂O₃ and TPODAC particles are evenly distributed on the surface of the organic magnetic bentonite 150-TPMB. The bentonite lamellae in 150-TPMB become more loose, and the edges and corners are smoothed by the organic carbon chains coating the bentonite lamellae. The high modification ratio causes the bentonite surface to appear molten, indicating that a large number of surfactant molecules are loaded onto the MB surface and that the interlayers of the bentonite are encapsulated by these surfactants. Furthermore, due to the increased van der Waals forces between the TPMB particles, the particles become more tightly connected and the agglomeration is more pronounced.

[0072] Performance Testing

[0073] Through VSM analysis ( Figure 1 ). After RB was modified with γ-Fe₂O₃ particles and TPODAC, the magnetic hysteresis loop of 150-TPMB was free of hysteresis loops, indicating superparamagnetism. The saturation magnetization intensity reached approximately 43.93 emu / g, exceeding the minimum saturation magnetization intensity (16.3 emu / g) recovered by separation using an external magnetic field. This indicates that 150-TPMB can be separated from solution using a permanent magnet. Experiments have also shown that 1g of 150-TPMB is attracted by a permanent magnet within 20 seconds, achieving rapid separation from water.

[0074] By TG analysis ( Figure 2 ), the weight loss rate of the adsorbed water and interlayer water loss peaks appeared in the range of 30-200℃, with little change, resulting in a mass loss of 1.12%. Three pyrolysis weight loss peaks appeared in the range of 200-800℃, with mass loss values ​​of 6.33%, 2.06% and 1.22%, respectively. The appearance of the first pyrolysis weight loss peak (200-300℃) is due to the electrostatic interaction between TPODAC molecules on the outer surface of MB (outside the interlayer space) and MB. The second mass loss occurred between 300-450℃, presumably because TPODAC is mainly located at the edge of the layer and is covalently bonded to MB. When the temperature rose to 700℃, the metal oxides attached to the surface particles showed mass loss due to heat treatment. During the entire process from 30℃ to 800℃, the mass loss of 150-TPMB was 10.76%, and 89.24% of the mass residue was detected.

[0075] By FTIR analysis ( Figure 3 ), the FTIR spectrum of RB changed after γ-Fe2O3 loading, 3450cm -1 The frequency of the band near RB is lower than that of RB, which is speculated to be due to the interaction between Fe-O band and Si-O band, and γ-Fe2O3 has been well incorporated into the RB structure. Compared with MB, TPMB with different TPODAC modification ratios has a high peak at 2921cm -1 、2851cm -1 、1470cm -1 Three additional absorption bands can be observed at both ends of the spectrum, which correspond to the presence of TPODAC, methyl (—CH3) at 2960 cm -1 and 2870cm -1 There are asymmetric and symmetric tension vibrations at 1470 cm -1 The strain vibration at is caused by the bending vibration of the C—H bond of the methylene (—CH2) group. When TPODAC binds to MB, the wavenumber shifts to a higher direction.

[0076] By XRD analysis ( Figure 4 ), MB and 150-TPMB showed obvious maghemite structure (γ-Fe2O3, JCPDS No. 39-1346), with 2θ peaks at 26.10°, 30.24°, 35.63°, 43.28°, 53.73°, 57.27° and 62.93°, corresponding to the (211), (220), (311), (400), (422), (511) and (440) crystal planes, respectively.

[0077] Test Example 1

[0078] This test example analyzes the adsorption isotherms of pretilachlor by the organically modified magnetic bentonites with different organic modification ratios prepared in Examples 1 to 3. The specific steps are as follows:

[0079] (1) Preparation of simulated wastewater: Prepare a pretilachlor stock solution using acetonitrile. Dissolve 250 mg of pretilachlor in acetonitrile and dilute to 250 mL to prepare a pretilachlor standard stock solution with a concentration of 1 g / L. Store in a fluorinated HDPE reagent bottle.

[0080] (2) Experimental water: The standard mother solution of pretilachlor obtained in step (1) was diluted to prepare 40 mL of simulated wastewater containing 4 to 100 mg / L pretilachlor, and the pH of the simulated wastewater was adjusted to 7 using 0.01 mol / L NaOH solution and 0.02 mol / L HCl.

[0081] (3) Adsorbent: 40 mg of the organically modified magnetic bentonite prepared in Examples 1-3 was added to simulated wastewater containing different concentrations of pretilachlor, so that the concentration of the adsorbent in the simulated wastewater was 1 g / L.

[0082] (4) Adsorption experiment: The simulated wastewater containing pretilachlor and organically modified magnetic bentonite was placed in a water bath constant temperature oscillator at 25 °C for 5 h to reach adsorption equilibrium. Under the action of an external magnet, 1 mL of the supernatant was taken into a syringe and filtered through a 0.22 μm nylon filter membrane. The equilibrium concentration of the solution was determined using HPLC.

[0083] like Figure 5 As shown, the equilibrium adsorption capacity of TPMB increases with increasing pretilachlor concentration. Furthermore, the saturated adsorption capacity is also related to the amount of TPODAC modification on TPMB: increasing the modification amount also increases the saturated adsorption capacity for different concentrations of pretilachlor. The saturated adsorption capacity of 150-TPMB prepared in Example 3 under these experimental conditions reached 52.16 mg / g.

[0084] Test Example 2

[0085] This test example analyzes the removal effect of organically modified magnetic bentonites with different organic modification ratios prepared in Examples 1 to 3 on pretilachlor at different pH values. The specific steps are as follows:

[0086] (1) Preparation of simulated wastewater: Prepare a pretilachlor stock solution using acetonitrile. Dissolve 250 mg of pretilachlor in acetonitrile and dilute to 250 mL to prepare a pretilachlor standard stock solution with a concentration of 1 g / L. Store in a fluorinated HDPE reagent bottle.

[0087] (2) Experimental water: Dilute the standard pretilachlor stock solution obtained in step (1) to prepare 40 mL of simulated wastewater containing 100 mg / L pretilachlor. Set six different pH values ​​and adjust the pH of the simulated wastewater to 2-10 using 0.01 mol / L NaOH solution and 0.02 mol / L HCl.

[0088] (3) Adsorbent: 40 mg of the organically modified magnetic bentonite prepared in Examples 1-3 was added to simulated wastewater at different pH values, respectively, to make the concentration of the adsorbent in the simulated wastewater 1 g / L.

[0089] (4) Adsorption experiment: The simulated wastewater containing pretilachlor and organically modified magnetic bentonite was placed in a water bath constant temperature oscillator at 25 °C for 5 h to reach adsorption equilibrium. Under the action of an external magnet, 1 mL of the supernatant was taken into a syringe and filtered through a 0.22 μm nylon filter membrane. The equilibrium concentration of the solution was determined using HPLC.

[0090] like Figure 6 As shown, the organically modified magnetic bentonite achieves optimal adsorption at a pH of 7, with the 150-TPMB prepared in Example 3 achieving a removal efficiency of 52.16% for pretilachlor. Within the pH range of 2-10, the adsorption capacity of TPMB for pretilachlor does not vary by more than 10 mg / L, demonstrating that TPMB has relatively stable adsorption performance for pretilachlor over a wide pH range and is suitable for the removal of pretilachlor in acidic or alkaline water.

[0091] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.

Claims

1. An organic modified magnetic bentonite, characterized in that: The organic modified magnetic bentonite is a ternary composite material which uses bentonite as a carrier, loads γ-Fe2O3 magnetic particles, and uses an organic modifier 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride for surface modification.

2. A method for preparing the organic modified magnetic bentonite according to claim 1, characterized in that: The method adopts a coprecipitation method to prepare magnetic γ-Fe2O3 particles, and then loads the particles onto bentonite to obtain magnetic bentonite, and then uses 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride for surface modification to obtain organically modified magnetic bentonite.

3. The method for preparing an organic modified magnetic bentonite according to claim 2, characterized in that: The specific steps of the method for preparing the organic modified magnetic bentonite are as follows: S1, preparing RB dispersion; S2, preparation of Fe 2+ and Fe 3+ A mixed solution; S3, preparation of magnetic bentonite: the Fe-containing 2+ and Fe 3+ The mixed solution is added to the RB dispersion prepared in step S1, the pH is adjusted, magnetic stirring is performed under heating conditions in a water bath, and the mixture is filtered and washed, and dried to obtain a magnetic bentonite loaded with γ-Fe2O3; S4, preparing a mixed dispersion: dissolving the magnetic bentonite prepared in step S3 in a solvent, adding 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride after ultrasonication, and obtaining a mixed dispersion after a second ultrasonication; S5, preparing organic modified magnetic bentonite: stirring and condensing the mixed dispersion prepared in step S4 under water bath heating conditions, filtering, washing, and drying to obtain organic modified magnetic bentonite.

4. The method for preparing an organic modified magnetic bentonite according to claim 3, characterized in that: In step S1, the preparation method of the RB dispersion is as follows: Unmodified bentonite was dispersed in deionized water and magnetically stirred under water bath heating conditions to form RB dispersion; The solid-liquid ratio of the bentonite and deionized water is 1:(5-10), The water bath heating temperature is 40-60° C., and the magnetic stirring time is 30-40 min.

5. The method for preparing an organic modified magnetic bentonite according to claim 3, characterized in that: In step S2, the Fe 2+ and Fe 3+ The preparation method of the mixed solution is as follows: Ferrous sulfate heptahydrate and ferric chloride hexahydrate are dissolved in deionized water to form a Fe 2+ and Fe 3+ of mixed solution.

6. The method for preparing an organic modified magnetic bentonite according to claim 5, characterized in that: The mixed solution contains Fe 2+ with Fe 3+ The molar ratio is 1:(1.5~2.5).

7. The method for preparing an organic modified magnetic bentonite according to claim 3, characterized in that: In step S3, the Fe 2+ and Fe 3+ The volume ratio of the mixed solution to the RB dispersion prepared in step S1 is 1:(1-2); The pH regulator is concentrated ammonia and hydrochloric acid, and the pH adjustment range is 10 to 12; The water bath heating temperature is 50-70°C, and the magnetic stirring time is 50-70min; The detergent is deionized water; The drying temperature is 60-80° C., and the drying time is 20-30 hours.

8. The method for preparing an organic modified magnetic bentonite according to claim 3, characterized in that: In step S4, the solid-liquid ratio of the magnetic bentonite and the solvent is 1:(90-110); The solvent is an ethanol / water solution, and the volume ratio of the ethanol to water is (2-4):1; The cation exchange capacity of the magnetic bentonite is 498.26-523.40 mmol / kg; The mass concentration of the 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride is 50% to 70%; The dosage of the 3-(trimethoxysilyl)propyl-N-octadecyldimethylammonium chloride is 20%-150% of the cation exchange capacity of the magnetic bentonite; The ultrasonic time is 30 to 50 minutes, the secondary ultrasonic time is 20 to 40 minutes, and the ultrasonic frequency is 30 to 50 kHz.

9. The method for preparing an organic modified magnetic bentonite according to claim 3, characterized in that: In step S5, the water bath heating temperature is 50-70° C., the stirring time and the condensation reflux time are 4-6 hours, The washing solvent is an ethanol / water solution, and the volume ratio of the ethanol to water is (2-4):1; The drying temperature is 20-40° C., and the drying time is 20-30 hours.

10. A use of the organic modified magnetic bentonite as claimed in claim 1, characterized in that: The organic modified magnetic bentonite is used for adsorbing pretilachlor.

Citation Information

Patent Citations

  • Organically Modified Magnetic Alkaline Calcium-Based Bentonite and Its Preparation Method

    CN108114694B

Cited By

  • Low-carbon drainage polyurethane adhesive and preparation method thereof

    CN120699577A